Asymmetric cloning of steering, quantum discord, and coherence - Irina Ion; Iulia Ghiu (Results in Physics)
Cloning of steering, quantum discord, and coherence is investigated by using two types of cloners: local and nonlocal 1→2 optimal universal asymmetric cloning machines. We prove the impossibility of generating two steerable output states when local cloners are used. On the other hand, when nonlocal cloning machines are employed, we show that there are ranges of the parameters which characterize the initial state and the cloning machines, such that the two output mixed states are steerable. Moreover, we obtain analytical expressions of the quantum discord and the coherence of the two output states generated by local and nonlocal asymmetric cloners. Further we make a detailed comparison of steering, quantum discord, and coherence of the output states obtained by local versus nonlocal cloning machines.